LITERASI ETIS PENGGUNAAN ARTIFICIAL INTELLIGENCE BAGI PEMUDA GBI SE-PROBOLINGGO DALAM PELAYANAN DAN TRANSFORMASI SOSIAL - Frans Pantan; Anggi Maringan Maringan Hasiholan; Ferdinand Edu; Priskila Issak Benyamin; Allen Jordi Ibrani (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
The development of Artificial Intelligence (AI) presents both opportunities and ethical challenges for church life, particularly in youth ministry. AI can be utilized to support the preparation of ministry materials, digital content production, church communication, faith formation, and the design of social programs. However, its use also raises concerns related to information accuracy, algorithmic bias, plagiarism, data privacy, technological dependency, and the weakening of theological reflection in ministry. This community service program aimed to strengthen ethical AI literacy among GBI youth across Probolinggo in the contexts of ministry and social transformation. The program employed a Service Learning model based on ethical AI literacy through five stages: problem orientation, AI literacy instruction, guided practice, ethical-theological reflection, and the development of ministry action plans. The program involved 35 participants. The evaluation results showed an increase in participants’ understanding, with the average pre-test score rising from 56.8 to 84.1 in the post-test, indicating a gain of 27.3 points. In addition, 91.4% of participants stated that AI should be treated as a supporting tool rather than a substitute for human agency in ministry, while 88.6% emphasized the importance of verifying AI-generated information before use. The participants also produced seven AI-based action plans for digital ministry, faith formation, data privacy education, anti-hoax campaigns, and social transformation. These findings indicate that ethical AI literacy through a Service Learning model can strengthen the understanding, ethical awareness, and practical skills of church youth in using technology responsibly for ministry and society.